Socio-demographic, health-related and psychosocial correlates of fear of falling and avoidance of activity in community-living older persons who avoid activity due to fear of falling - Delbaere Kim; McKee Kevin J; van Haastregt Jolanda CM; Kempen Gertrudis IJM; Zijlstra GA Rixt (BMC, 2009)
Abstract Background Fear of falling and avoidance of activity are common in old age and are suggested to be (public) health problems of equal importance to falls. Earlier studies of correlates of fear of falling and avoidance of activity did hardly differentiate between severe and mild levels of fear of falling and avoidance of activity which may be relevant from clinical point of view. Furthermore, most studies focused only on socio-demographics and/or health-related variables and hardly incorporated an extensive range of potential correlates of fear of falling including psychosocial variables. This study analyzes the univariate and multivariate associations between five socio-demographic, seven health-related and six psychosocial variables and levels of fear of falling and avoidance of activity in older persons who avoid activity due to fear of falling. Methods Cross-sectional study in 540 community-living older people aged ≥ 70 years with at least mild fear of falling and avoidance of activity. Chi-squares, t-tests and logistics regression analyses were performed to study the associations between the selected correlates and both outcomes. Results Old age, female sex, limitations in activity of daily living, impaired vision, poor perceived health, chronic morbidity, falls, low general self-efficacy, low mastery, loneliness, feelings of anxiety and symptoms of depression were identified as univariate correlates of severe fear of falling and avoidance of activity. Female sex, limitations in activity of daily living and one or more falls in the previous six months correlated independently with severe fear of falling. Higher age and limitations in activity of daily living correlated independently with severe avoidance of activity. Conclusion Psychosocial variables did not contribute independently to the difference between mild and severe fear of falling and to the difference between mild and severe avoidance of activity due to fear of falling. Although knowledge about the unique associations of specific variables with levels of severe fear of falling and avoidance of activity is of interest for theoretical reasons, knowledge of univariate association may also help to specify the concepts for developing interventions and programmes to reduce fear of falling and avoidance of activity in old age, particularly in their early stages of development.